A classification scheme for project scheduling problems - HERROELEN, Willy (Institutional Knowledge at Singapore Management University, 1999)
The basic concern of scheduling is commonly described as the allocation of limited resources to tasks over time (Lawler et al. 1993, Pinedo 1995). The resources and tasks may take many forms. In project scheduling the tasks refer to the activities belonging to one or more projects. The execution of project activities may require the use of different types of resources (money, crews, equipment, …). The scheduling objectives may also take many forms (minimizing project duration, minimizing project costs, maximizing project revenues, optimizing due date performance,…). The result is a wide and steadily growing variety of problem types which motivates the introduction of a systematic notation that can serve as a basis for a classification scheme.